TRANSFORMASI TATA KELOLA DAN AKUNTABILITAS ADMINISTRASI NEGARA DALAM OPTIMALISASI KINERJA BADAN USAHA MILIK NEGARA (BUMN) MELALUI IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE DI ERA REFORMASI BIROKRASI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
This study analyses the transformation of governance and accountability in state administration in optimising the performance of state-owned enterprises (SOEs) through the implementation of Good Corporate Governance (GCG) principles in the era of bureaucratic reform in Indonesia. Using a systematic literature review approach, the study identifies synergies between the New Public Management paradigm and the five principles of GCG—transparency, accountability, responsibility, independence, and fairness—which have been proven to improve SOE financial performance indicators such as ROA, ROE, and dividend contributions to the state budget. The main findings show that national bureaucratic reform has created a hybrid governance ecosystem that minimises political conflicts of interest, strengthens external oversight by the State Audit Agency (BPK) and the Corruption Eradication Commission (KPK), and supports the digitisation of governance for operational efficiency. Although bureaucratic cultural challenges and regulatory duality still exist, this model has proven effective through case studies of Telkom and Pertamina, making it a best practice for optimising state-owned corporations in developing countries.